2019
DOI: 10.1002/eat.23151
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes in treated males with anorexia nervosa and bulimia nervosa—A prospective, gender‐matched study

Abstract: Objective We report on the long‐term outcome of males compared to females treated for anorexia nervosa (AN) or bulimia nervosa (BN). Methods A total of 119 males with AN and 60 males with BN were reassessed 5.8 ± 4.6 and 7.5 ± 5.9 years (respectively) after treatment and compared to matched female patients. Results At follow‐up, males with AN had a higher body weight than females. For AN, remission rates (40% males vs. 41% females) did not differ at follow‐up. And at follow‐up, more males (34%) than females (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 50 publications
6
33
1
Order By: Relevance
“…Most [13][14][15][16][17][18][19], but not all [20], have identified longer duration of illness as a predictor of worse long-term outcome. Body mass index (BMI) is also related to outcome: most studies show associations between lower admission and discharge BMI and worse outcomes in adults [11,14,16,17,[21][22][23][24][25], though research in adolescents suggests discharge BMI is less predictive of outcome when inpatient treatment is followed by structured outpatient treatment [26,27]. AN subtype has also been associated with outcome, though this has not been a consistent finding [18,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most [13][14][15][16][17][18][19], but not all [20], have identified longer duration of illness as a predictor of worse long-term outcome. Body mass index (BMI) is also related to outcome: most studies show associations between lower admission and discharge BMI and worse outcomes in adults [11,14,16,17,[21][22][23][24][25], though research in adolescents suggests discharge BMI is less predictive of outcome when inpatient treatment is followed by structured outpatient treatment [26,27]. AN subtype has also been associated with outcome, though this has not been a consistent finding [18,28].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies on inpatient samples specifically have tended toward examining predictors of outcome unrelated to treatment (e.g., age of onset, comorbidities, family support) and report overall prognosis categorically [42][43][44][45][46][47]. Fewer have studied continuous outcomes, such as weight, symptoms, and overall clinical impairment over time [13,23,38,48,49], and these have generally been limited to short-term follow up [13,19,49] or to a single assessment point [23,25,34]. Together, these studies suggest that higher BMI at discharge and shorter duration of illness are important factors in the course of AN.…”
Section: Introductionmentioning
confidence: 99%
“…These males (27 AN, 50 BN, 103 ED‐NOS) were included in the present study. Seven males with AN and six males with BN died after participating in follow‐up assessment and were included in analysis for mortality and for follow‐up (Strobel, Quadflieg, Naab, Voderholzer, & Fichter, under review).…”
Section: Methodsmentioning
confidence: 99%
“…As such, the application of clinical interventions with male populations rests on inferences drawn from research conducted with largely female samples. However, in the largest prospective study to date of treatment outcomes in males with eating disorders, Strobel, Quadflieg, Naab, Voderholzer, and Fichter () and Quadflieg, Strobel, Naab, Voderholzer, and Fichter () describe a series of important outcomes in a large sample of male inpatients with eating disorders over an average follow‐up period ranging from ~5 to 9 years across the diagnostic groups.…”
Section: Treatment Outcomes In Malesmentioning
confidence: 99%
“…In assessing long‐term treatment outcomes among 119 men with anorexia nervosa and 60 men bulimia nervosa, Strobel et al () noted that males with anorexia nervosa demonstrated comparable rates of remission to females with anorexia nervosa treated in the same program (male remission rate: 40%, female remission rate: 41%), and typically demonstrated greater body weight. Among male inpatients with bulimia nervosa, remission rates were slightly lower at long‐term follow (44%) relative to female inpatients treated in the same program (50%).…”
Section: Treatment Outcomes In Malesmentioning
confidence: 99%